2013
DOI: 10.1021/jm401546n
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 1-Methyl-1H-imidazole Derivatives as Potent Jak2 Inhibitors

Abstract: Structure based design, synthesis, and biological evaluation of a novel series of 1-methyl-1H-imidazole, as potent Jak2 inhibitors to modulate the Jak/STAT pathway, are described. Using the C-ring fragment from our first clinical candidate AZD1480 (24), optimization of the series led to the discovery of compound 19a, a potent, orally bioavailable Jak2 inhibitor. Compound 19a displayed a high level of cellular activity in hematopoietic cell lines harboring the V617F mutation and in murine BaF3 TEL-Jak2 cells. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 40 publications
(64 reference statements)
1
41
0
Order By: Relevance
“…In the current study, CIMO showed potent anticancer activity via the JAK2-STAT3 pathway; hence, we considered the possibility that CIMO interacts with the kinase domain of JAK2 directly. Thus, the JAK2 inhibitor 1-methyl-1H-imidazole, which modulated the JAK/STAT pathway, was considered for our studies (20). A molecular docking study was carried out to examine the possibility of CIMO binding to the kinase domain of JAK2.…”
Section: Cimo Suppresses the Growth Of Human Hcc In Vivo And Stat3 Acmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, CIMO showed potent anticancer activity via the JAK2-STAT3 pathway; hence, we considered the possibility that CIMO interacts with the kinase domain of JAK2 directly. Thus, the JAK2 inhibitor 1-methyl-1H-imidazole, which modulated the JAK/STAT pathway, was considered for our studies (20). A molecular docking study was carried out to examine the possibility of CIMO binding to the kinase domain of JAK2.…”
Section: Cimo Suppresses the Growth Of Human Hcc In Vivo And Stat3 Acmentioning
confidence: 99%
“…The docking scores of the biologically active ligands with the kinase domain of JAK2 (Protein Data Bank entry 4C61) are summarized (Fig. 8A) (20). Based on Ligand Fit docking score calculations, CIMO shows a docking score of 95.07 kcal/mol, which is higher when compared with other structurally related azaspiranes.…”
Section: Cimo Suppresses the Growth Of Human Hcc In Vivo And Stat3 Acmentioning
confidence: 99%
See 1 more Smart Citation
“…JAK2 is a member of Janus kinase and provides instructions for making a protein that promotes the growth and division (proliferation) of cells. In this study, the JAK2 was used as receptor and the chemical compounds used in herbal as the ligand [24]. This study will be based on the modification of our previously developed method [25][26][27].…”
Section: Mustarichie Et Almentioning
confidence: 99%
“…AstraZeneca recently reported an improved JAK2 inhibitor developed from AZD1480 [43]. Two major modifications were made to the original AZD1480 structure: first, the aminopyrazole on pyrimidine C4 was changed to aminoimidazole, which is expected to give the same binding interactions as AZD1480 to the hinge region of the ATP-binding site; second, the hydrophobic pocket of the pyrimidine ring was occupied with a fused bicyclic ring system.…”
Section: Key Termmentioning
confidence: 99%